The moving axis in children’s education: a planning project - Joceli do Carmo Knebel da Costa; Amauri Aparecido Bassoli de Oliveira (Journal of Physical Education (Maringá), 2008)
This paper aims at organizing a planning project for the Physical Education curricular activity, the “moving” axis in children’s education. The study discusses about children’s education, emphasizes children’s motor, biological and social characteristics from 4 to 6 years old, and also suggests an organization of contents/acitivities to be developed in such educational stage. In order to help in infant development the Physical Education professional needs to know his / her pupils, their necessities and interests so that to provide a full of experience environment which may benefit the construction of participatory and critical human beings with autonomy in relation to their motor world.